Enhancing the mechanical properties and surface morphology of individualized Ti-mesh fabricated through additive manufacturing for the treatment of alveolar bone defects - Wang, Lingxu; Wang, Fangfang; Ayisen, Saimi; Ren, Tianshui; Luo, Xiaoping; Wang, Penglai (Frontiers in Bioengineering and Biotechnology, 2023)
This study aimed to explore the impact of heat treatment (HT) and synergistic finishing technology of electric field and flow field (EFSF) on the properties of titanium meshes commonly used in biomedical applications. Our results demonstrated that the innovative EFSF technique, coupled with HT, significantly enhanced the surface properties of titanium meshes, including uniformity, controllability, and biocompatibility. The HT induced a fusion of grains and a reduction of surface pores, leading to improved tensile and elongation properties. EFSF further augmented these enhancements by substantially reducing surface roughness and removing adhered titanium powder, a byproduct of selective laser melting printing. The titanium mesh demonstrated improved mechanical properties after undergoing HT treatment. Its hydrophilicity and surface-free energy were enhanced after treatment with EFSF. Moreover, the surface of the titanium mesh treated with EFSF noticeably reduced bacterial adhesion and was nontoxic to osteoblast proliferation. This enhanced its applicability in clinical alveolar bone augmentation.